Stimuli towards well-being in an environment with Complementary and Integrative Practices (CIPs) - Villela, Mariana Silva; Bins Ely, Vera Helena Moro (Ambiente Construído, 2020)
This article presents a proposal to categorise stimuli that influence well-being in therapeutic environments following Complementary and Integrative Practices (CIPs). With the broader aim of understanding which environmental stimuli influence the well-being of CIP therapeutic environment users, this qualitative research adopted a multimethod approach: bibliographic and documentary research; walkthrough analysis; exploratory visits; environment observations; and finally, interviews. After cross-referencing a literature review and an environmental assessment of three case studies during 2017, a categorisation was drawn up, and it suggests that the stimuli which most influence well-being in CIP environments are: Artistic, Auditory, Biological, Luminous and Hygrothermal Comfort, Energetic, Spatial, Natural, Olfactory, Social and Socio-Spatial stimuli. Included in a broader debate on creating environments favourable to users’ health, and in line with an increasing demand of CIPs in Brazil, this categorisation aims at contributing to the knowledge of CIP environment-specific necessities and improving the quality from the early stage of project idealisation.